SiAlON–epoxy nanocomposite coatings: Corrosion and wear behavior. Issue 35 (18th May 2016) - Moradi, M. H.; Aliofkhazraei, M.; Toorani, M.; Golgoon, A.; Rouhaghdam, A. Sabour
ABSTRACT: In this study, epoxy powder as a matrix was combined with different contents of silicon–aluminum–oxygen–nitrogen (SiAlON) nanoparticles using a planetary ball mill. Pure epoxy and nanocomposite powders were applied on the surface of plain carbon steel components by the electrostatic spraying method. Curing of the coatings was done in an oven or microwave for the appropriate time. The coating structure and morphology of the SiAlON nanoparticles were studied by scanning electron microscopy and transmission electron microscopy, respectively. The corrosion properties of the coatings were assessed by immersion, Tafel polarization, and electrochemical impedance spectroscopy tests in 3.5% NaCl solution. The results show that addition of 10 wt % SiAlON nanoparticles markedly increases the corrosion resistance of epoxy coatings. Thus, it can be inferred that the corrosion rate of these coatings is 15 to 18 times lower than that of pure epoxy samples and 8 to 11 times lower than coatings with 20 wt % SiAlON. The higher corrosion resistance of nanocomposite coatings can be attributed to the barrier properties of SiAlON nanoparticles. The tribological performance of the coatings was studied with the pin‐on‐disk test. The results of wear testing show that the samples containing 10 wt % SiAlON provide about five times more wear resistance than pure ones and about two times more than coatings with 20 wt % SiAlON. However, the coefficient of friction for nanocomposite coatings is reduced about 50% compared to the pure sample. Also, the curing process in either regime (oven or microwave) has the same effect on the corrosion and wear properties, and the coatings are completely crosslinked. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43855. Abstract :